AN ANALYSIS OF THE BUSINESS FEASIBILITY OF FROZEN PINEAPPLE PRODUCTS (Ananas comosus) IN MARDI SERDANG SELANGOR MALAYSIA - Damanik, Shela Santika; Salsabila; Masdek, Nik Rozana Nik Mohd; Ying, Joanna Cho Ler (Universitas Veteran Bangun Nusantara, 2025)
Pineapple (Ananas comosus) belongs to the tropical fruit group because pineapple is not a seasonal fruit, its price is consistent and affordable. The pineapple industry in Malaysia is between industries under the agrofood sector that play an important role in supporting the country's development progress, including the socioeconomic development of agricultural entrepreneurs. This study aims to evaluate costs, sales revenue, and profit, as well as to assess the Break Even Point (BEP), Revenue Cost Ratio (R/C), and Benefit Cost Ratio (B/C) in the frozen pineapple production business in MARDI, Serdang Selangor, Malaysia. The location in this study was at the Malaysian Agricultural Research and Development Institute (MARDI) Serdang. In this study, data was collected using observation methods on frozen pineapple products at MARDI Serdang Malaysia. In this study, the data used included primary and secondary data. Research results show total revenue of Rp. 79,200,000 and a total production cost of Rp. 57,686,544, the frozen pineapple fruit business business received a net income of IDR. 21.513.456. This shows significant business potential and an R/Cratio of 1.37 shows each production cost expenditure of Rp. 1 generates Rp. 1 income. 1,37. The value of B/Cratio is 0.37, which indicates that the frozen pineapple fruit business in MARDI Serdang is quite efficient and profitable, so it is worth continuing. Keywords: Agrifood, Ananas comosus, MARDI, Production Cost.